Dentigerous cyst (Heterotopic polydontia) in a horse - A case report - Tiago C. Peixoto; Vivian A. Nogueira; Mariana C. Oliveira; Ana Paula C. Pires; Cristiano C.P. Veiga; Mariana S. D’Avila; Bruno G. Souza; Ticiana N. França (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Peixoto T.C., Nogueira V.A., Oliveira M.C., Pires A.P.C., Veiga C.C.P., D’Ávila M.S., Souza B.G. & França T.N. [Dentigerous cyst (Heterotopic polydontia) in a horse - A case report.] Cisto dentígero (Polidontia Heterotópica) em equino - Relato de caso. Revista Brasileira de Medicina Veterinária, 38(Supl.2):139-142, 2016. Setor de Anatomia Patológica, Universidade Federal Rural do Rio de Janeiro, Rodovia BR-465 Km 7, Seropédica, RJ 23890-000, Brasil. E-mail: vivianmedvet@yahoo.com.br It is described a case of dentigerous cyst in a 2-year-old female pampa horse that showed swelling in the right temporal region and a draining tract near the right pinna. The diagnosis is established with clinical, radiographic and histopathological examination of the surrounding structures. Dentigerous cyst is an uncommon condition in horses and it occurs most frequently in young animals. Twelve 1,3-4 cm white firm structures were removed, some with central pulp canal and longitudinal grooves in the external surface, grossly resembling teeth. Microscopic examination showed a structure compatible with dental tissue lined by a non-keratinezed epithelium. A lympho-plasmocitary inflammatory reaction was also seem in the dermis. Differential diagnoses includes congenital deformities of the bone, trauma, abscess and perforating foreign bodies. Post- -operative complications include haemorrhage, fracture of the temporal bone and permanent neurological damage. This case highlights the importance of the investigation of recurrent abscess in horses that are resistant to antibiotics.